The Participation of Happy Laying Chicken with Iodine Supplementation Farmers Group in Samokhae Sub-district, Phitsanulok Province - Jaipong, Prapasiri; Kotham, Patthanun; Ngoc, Tuan Nguyen; Kaewkongsap, Adisak; Thongchai, Wisanu; Yaemkong, Sirikarnda; Yaemkong, Suphawadee (Area Based Development Research Journal, 2019)
The purpose of this research is to develop participation of happy laying chicken and iodine supplementation farmers group in Samokhae sub-district, Muang district, Phitsanulok province in order to enhance the ability to generate income and to strengthen the local economy. In particular, the ability to enable a group of farmers contributes to the sustainability of economy and society. The research team employed the participatory action research method with 30 laying chicken farmers and researcher students and staff from local administrative offices. The integrated framework is employed in this study to collaboratively drive the organization through observation, interview and participating meeting. The research aims to identify problems, obstacles, and needs of the farmers in happy laying chicken with iodine supplementation; and suggests the best practice to solve the problems. The findings suggest that 1) for the cost of feedings, the farmers should save up by buying raw ingredients and mix the feedings by themselves. 2) The marketing process can be extended to online channels like on a Facebook page. 3) The needs for processed eggs are responded by making herbs salted egg. For data analysis, 6 farms are selected by purposive sampling to represent the best farms. Their egg qualities, amount of iodine in eggs and average daily revenue from selling eggs before and after activity are compared by t-test at α= 0.05. The results show that egg qualities, amount of iodine in eggs and average revenue per day from selling eggs is significant at p<0.05. Moreover, this operation has led to potential establishment of the happy laying chicken with iodine supplementation farmer group in Samokhae sub-district community enterprise in the future. The key success factors contribute to community strengths and will lead to career development for the farmer group.